A developmental study of moral judgement of Brazilian children and adolescents - Biaggio, Angela M.B. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study attempted to replicate Kohlberg’s findings on development of moral judgment, with Brazilian 10, 13 and 16 year old subjects. Fifteen boys and 15 girls at each of the three age levels took three of Kohlberg’s moral judgment stones. Moral Maturity Scores (MMS) were analyzed by means o f a 2 X 3 analysis of variance. Factor age was found to be significant (F [g4= 3, 79, p < .05) revealing a trend for MMS to increase with age. Factor sex was also found to be significant (F1.84 = 10, 58, p < .011, with girls having higher MMS than boys. An analysis of the percentages of moral statements classified at each stage also confirmed Kohlberg’s data. The usage of stages I and 2 decreased with age, and usage of stages 4 and 5 increased with age. The main difference from Kohlberg’s U.S. findings was that Brazilian subjects at all three age levels were very high on stage 3 (“good-boy” morality) and not as high as expected, especially at age 16, on stage 4 (“law and order” morality). The data obtained with Brazilian subjects resemble those obtained by Kohlberg for Mexican subjects.